Entrepreneurial Competencies and Succession Planning among Family Business Owners in a Second-Class Municipality in Iloilo Province: An Explanatory Sequential Mixed Methods Study - Sobrevega, Elaine B.; Lopena, Grace L. (Philippine Social Science Journal, 2025)
Employing an explanatory sequential mixed-method design, this study assesses entrepreneurial competencies and succession planning among family business owners in a second-class Filipino municipality. The findings reveal that while owners possess high entrepreneurial competence, often enhanced by education, succession planning remains largely informal and inconsistent, particularly among younger, less experienced individuals. Statistical analysis confirms a strong correlation between these variables, significantly influenced by age and experience rather than gender. To address the scarcity of formal transition strategies, the study developed the “Business Continuity Compass,” a practical manual for ensuring business longevity to be used by owners and local licensing offices. Future research suggests replicating this study across other Iloilo localities and utilizing alternative qualitative designs to further validate these dynamics.